“Reality does not happen twice” : About the Autobiographic Moment in Leah Goldberg’s Poetry - Jean Baroukh, Rina (MiKAN, 2016)
The article examines a group of poems from Leah Goldberg’s first book, Smoke Rings (Taba’ot Ashan), in which there are speaking objects – a clock, a lamp, etc. It claims that these objects are not merely personified, but are given a voice and a face. This is a specific form of personification known as ‘prosopopoeia’, a trope Paul De Man examined in a well-known article and which this article makes use of. By creating this other presence inside the poem, a gaze is created. Goldberg creates gazes inside the poem that enable and define the reader’s gaze, upon the poem and upon the speaker. This gaze is both needed and rejected. The speaker cannot exist without it, yet it is also a critical, distanced gaze, that is incapable of truly grasping the speaker. This gaze is always needed, but it is also, always a disappointment. Interestingly, the mechanism described in this article, which operates in the group of poems with still objects, can also be seen in Goldberg’s love poems, thus making a correlation between the personification of the objects and the objectification of the loved one. This emphasizes the fictional aspect of Goldberg’s poetry and poetics, rendering readings that claim that her poetry is purely autobiographical more complex.